TRANSFORMATION OF HIGHER EDUCATION IN INDONESIA: PURSUING QUALITY, ACCESSIBILITY, AND RELEVANCE IN THE ERA OF GLOBALIZATION - Komari Komari; Rosi Fitriyanti S; Herry Wahyudi Susanto; Siminto; Amin (Adisam Publisher, 2023)
In the past, Indonesia's higher education system underwent a transformative journey marked by significant changes. The nation recognized the pivotal role of higher education in fostering socio-economic development and driving innovation. With a burgeoning young population and increasing demands for a skilled workforce, the importance of higher education institutions in shaping the nation's future became more evident than ever. The higher education landscape in Indonesia witnessed substantial growth and expansion. The government made considerable investments to enhance the quality and accessibility of higher education, aiming to compete effectively in the global knowledge economy. Despite these positive developments, critical issues related to quality, accessibility, and relevance emerged as significant challenges. This research, conducted in the past, aimed to explore these multifaceted challenges and propose strategies for improvement. The primary objectives were to examine the state of higher education in Indonesia, identify barriers hindering the delivery of high-quality and relevant education, assess the role of technology in reshaping higher education, explore the evolving needs of the job market, and provide recommendations to enhance the quality, accessibility, and relevance of higher education. The research findings contributed to the advancement of higher education in Indonesia, aligning it with the demands of the global knowledge economy. It emphasized the need for continued transformation to ensure that higher education institutions could effectively pursue quality, accessibility, and relevance in an era characterized by globalization and rapid change.